In Vitro effect of the ethanolic extract of Tephrosia Vogelii on Rhipicephalus Sanguineus in Abomey-Calavi - Dougnon Tossou Jacques; Adéhan Safiou; Houessionon Jédirfort; Farougou Souaïbou (Avicenna Journal of Phytomedicine, 2015)
Objectives: Ticks are vectors of several diseases, of which many are zoonosis transmissible to humans. The use of Tephrosia leafs’ extract as a low cost acaricide is spreading among farmers in central Kenya. Materials and Methods: The present study’s aim is to inventory endogenous control methods against dogs’ ticks among which Rhipicephalus sanguineus, in the Municipality of Abomey-Calavi. From September to October 2013, a survey was made on forty randomly selected breeders and ticks samples were collected on forty dogs. The web platform, www.epicollect.net, was used for the survey. In total, 77.5% (n=40) of examined dogs were infested with ticks Results: Three species of ticks were identified: Rhipicephalus sanguineus, Haemaphysalis leachi, and Amblyomma variegatum. They were found on 77.5%, 17.5%, and 15% of examined dogs, respectively. The numerical abundance of the three species was 87.06%, 11.9%, and 1.03%, respectively. The average number of ticks per animal was 16.83±5.04, 2.3±1.64, and 0.2±0.08 for Rhipicephalus sanguineus, Haemaphysalis leachi, and Amblyomma variegatum, respectively. Farmers used manual diptank (67.5%), plant ash (37.5%), petroleum (12.5%), motor oil (2.50 %), and sea water (7.5%) to fight against ticks. Conclusions: The phytochemical screening of the leafy stem’s powder of Tephrosia vogelii revealed the presence of catechol tannins, saponins, sugars, leuco-anthocyanins, polyterpenes, and sterols. A 100% larval mortality was observed at the concentration of 20% the ethanolic extract of the leafy stem of Tephrosia vogelii. The LC50 of this ethanolic extract against Rhipicephalus sanguineus larvae was equal to 2.6%.